The effect of deacetylation temperature on quality crab chitosan (Portunus pelagicus) - Ula, Mosriula; Anshar, Anshar; Karyawati, Karyawati; Samsibar, Samsibar; Rakhfid, Abdul; Rochmady, Rochmady (Sangia Research Media and Publishing, 2025)
Crab (Portunus pelagicus) is a fishery export commodity, especially to Japan, the European Union and the United States. On the other hand, the crab part, namely the shell, is still not utilized optimally so it becomes waste. To make crab shells valuable, several studies have revealed the presence of useful substances known as chitin and chitosan. Therefore, this research was carried out with the aim of knowing the effect of deacetylation temperature on the quality of chitosan and the optimal deacetylation temperature so as to produce good quality chitosan. Method: This study employs an experimental methodology based on Fully Randomized Design (CRD) analysis. Several deacetylation temperature treatments (00C, 900C, 950C, 1000C, 1050C, 1100C, 1150C, 1200C) were repeated three times in this study's design. Analyses of yield, moisture content, ash content, protein content, and acetyl content serve as test parameters. Result: The results showed that the treatment using different deacetylation temperatures had a very significant effect (Fcrit > Ftable 1%) on water content, ash content, protein content, acetyl content and had no significant effect (Fcrit > Ftable 5%) on the yield. The optimal deacetylation temperature was 1200C, with a yield of 19.050%, water content of 8.340%, ash content of 0.022%, protein content of 0.198%, and acetyl content of 84.870%. Conclusion: The conclusion based on analysis that the best temperature deacetylation in producing quality chitosan crab is 1200C.